FROM KITCHEN TO DIPLOMACY: KOREAN CUISINE AS SOFT POWER - Gadis Hilmi Nabiilah Rose; Alia Rahmatulummah; Siti Mardanita (Universitas Budi Luhur, 2025)
Abstract: The rise of digital technology has reshaped the global communication landscape, shifting public diplomacy from traditional physical spaces to more interactive virtual platforms. Within this context, gastrodiplomacy—the use of food as a medium for cultural exchange has become a strategic tool for nation branding and soft power. South Korea stands out as a success case, integrating its culinary traditions with the Korean Wave (Hallyu) to promote national identity and foster positive international perceptions. Through digital platforms like YouTube, Instagram, and Netflix, various Korean cuisines is not only introduced to global audiences but also emotionally engages, particularly in countries like Indonesia. Despite its growing relevance, the specific role of Korean gastrodiplomacy in shaping cultural identity in Indonesia remains underexplored. This study addresses that gap by examining how South Korea leverages culinary diplomacy within digital ecosystems to construct a favorable cultural image. The research employs a qualitative approach, analyzing digital content, media campaigns, and audience reception in Indonesia to understand the dynamics between food, culture, and perception. Findings suggest that the synergy between Korean cuisine and digital media creates dynamic cross-cultural spaces where emotional connections are built through shared experiences. Food, in this context not just as a consumable item but as a narrative tool that conveys values, traditions, and identity. Consequently, Korean gastrodiplomacy emerges as a powerful instrument of soft power, enhancing South Korea’s cultural presence and influence in Indonesia. This study concludes that culinary diplomacy, when effectively mediated through digital platforms, plays a significant role in contemporary cultural diplomacy. Abstrak: Kemajuan teknologi digital telah membentuk ulang lanskap komunikasi global, menggeser diplomasi publik dari ruang fisik tradisional ke platform virtual yang lebih interaktif. Dalam konteks ini, gastrodiplomasi—penggunaan makanan sebagai media pertukaran budaya—telah menjadi alat strategis untuk membangun citra bangsa dan kekuatan lunak (soft power). Korea Selatan menonjol sebagai contoh keberhasilan, dengan mengintegrasikan tradisi kulinernya ke dalam Gelombang Korea (Hallyu) guna mempromosikan identitas nasional dan membentuk persepsi internasional yang positif. Melalui platform digital seperti YouTube, Instagram, dan Netflix, berbagai jenis kuliner Korea tidak hanya diperkenalkan kepada audiens global, tetapi juga membangun keterikatan emosional, terutama di negara-negara seperti Indonesia. Meskipun semakin relevan, peran spesifik gastrodiplomasi Korea dalam membentuk identitas budaya di Indonesia masih belum banyak diteliti. Studi ini berupaya mengisi kekosongan tersebut dengan meneliti bagaimana Korea Selatan memanfaatkan diplomasi kuliner dalam ekosistem digital untuk membangun citra budaya yang menguntungkan. Penelitian ini menggunakan pendekatan kualitatif, dengan menganalisis konten digital, kampanye media, dan respons audiens di Indonesia guna memahami dinamika antara makanan, budaya, dan persepsi. Temuan menunjukkan bahwa sinergi antara kuliner Korea dan media digital menciptakan ruang lintas budaya yang dinamis, di mana keterikatan emosional terbentuk melalui pengalaman bersama. Dalam konteks ini, makanan tidak hanya menjadi barang konsumsi, tetapi juga alat naratif yang menyampaikan nilai, tradisi, dan identitas. Dengan demikian, gastrodiplomasi Korea muncul sebagai instrumen soft power yang kuat, yang memperkuat kehadiran dan pengaruh budaya Korea Selatan di Indonesia. Studi ini menyimpulkan bahwa diplomasi kuliner, ketika dimediasi secara efektif melalui platform digital, memainkan peran penting dalam diplomasi budaya kontemporer.